Factors Associated with Students’ Mental Health in Vocational High Schools - Putra, Hanif Marisa; Anita, Fitri; Andora, Novika (Inspirasi Foundation, 2026)
Introduction: Mental health is a crucial aspect of adolescents’ well-being, as this developmental stage involves significant physical, emotional, and social changes that increase vulnerability to psychological problems. Global and national data indicate a high and growing prevalence of mental health issues among adolescents, including anxiety, depression, bullying-related distress, and the negative impacts of excessive social media use. Parenting styles, experiences of bullying, and patterns of social media use are key factors that may significantly influence adolescents’ mental health and require further investigation. Objective: The purpose of this study was to determine the relationship between parenting patterns, bullying and social media on the mental health of students at SMK Negeri 1 Tukak Sadai, South Bangka Regency in 2025. Method: The design in this study used cross-sectional with independent variables (parenting patterns, bullying and social media) and dependent variables (student mental health). The population size in this study was 315 people and a sample of 83 people calculated using cluster sampling. The time of the study was May 5, 2025 Result: The results of the study using the Chi Square statistical test obtained a p-value for the parenting variable 0.000 <0.05, bullying 0.000 <0.05 and social media 0.000 <0.05. This shows that there is a significant relationship between parenting patterns, bullying and social media on the mental health of students at SMK Negeri 1 Tukak Sadai, South Bangka Regency in 2025. Conclusion: Suggestions in this study are expected to make School Health Effort activities a step in monitoring health and anticipating early detection of the risk of poor mental health.